Polyaniline Modified Magnetic Nanoparticles Coated With Dicationic Ionic Liquid For The Removal Of Rhodamine B And Extraction Of Polycyclic Aromatic Hydrocarbons - Shahriman, Mohamad Shariff Bin (2018)
In the present study, magnetic nanoparticles (MNPs) nanocomposites modified with polyaniline (PANI) coated with newly synthesized dicationic ionic liquid (DICAT) forming MNP-PANI-DICAT were successfully synthesized as a new generation material for magnetic solid phase extraction (MSPE). The synthesized materials were characterized using few techniques such as FT-IR, NMR, CHN, VSM, XRD, TGA, BET, SEM and TEM analysis. TEM revealed that particles size diameters distribution increased from MNPs (4.6 nm), MNP-PANI (5.0 nm) to MNP-PANIDICAT (6.8 nm). While, the surface area of BET analysis decreases from 96.9 m2 g-1 in MNPs to 45.2 m2 g-1 in MNP-PANI-DICAT. TGA analysis results showed that the presence of ionic liquids (ILs) increased the stability of the MNP-PANI-DICAT compared to MNP-PANI and native MNP.